Focusing on doctoral students’ experiences of engagement in the thesis work - Vekkaila, Jenna; Pyhältö, Kirsi; Lonka, Kirsti (Frontline Learning Research, 2013)
While doctoral students’ reasons for attrition and negative experiences have been explored for a long time, little is known about their engagement in their doctoral process. This study aimed at filling the gap in the doctoral education literature by exploring the nature of students’ engagement in doctoral work. Altogether, 21 behavioural sciences doctoral students from one top-level research community were interviewed. The interview data were qualitatively content analysed. The students described their engagement in terms of experiences of dedication, efficiency and sometimes absorption. The sources of their engagement were typically increased sense of competence and relatedness. They less often reported strengthened sense of autonomy and contribution as the sources. In addition, three qualitatively different experiences of engagement in doctoral work, adaptive engagement, agentic engagement and work-life inspired engagement were identified from the students’ descriptions. Further, there was a variation among the students in terms of what experiences of engagement they emphasized in different phases of their doctoral studies. Our results suggest that rather than being a singular entity doctoral student engagement in the doctoral work varies.